2009
DOI: 10.2190/iq.29.4.f
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Health Behavior regarding Hospital Waste Management in Dhaka, Bangladesh: A Dysfunctional Health Belief Model

Abstract: This article examined the usefulness of the Health Belief Model (HBM) and other confounding factors in determining health behavior of individuals involved in hospital waste management and tested four components of HBM in relation to demographic variables, knowledge, and occupational practices of the respondents. The study revealed that the waste pickers had a lower level of knowledge, attitude, and safe practices than nurses and sweepers. Perceived Susceptibility and Perceived Severity were moderately associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
2
4
1
Order By: Relevance
“…This finding in the present study contradicts the findings of other studies [24][25][26][27], which emphasized that the HBM variables overly depended on psychological factors rather than focusing on cultural values, myths, misconceptions and prejudices, which typically predict human behavior [28].…”
Section: Discussioncontrasting
confidence: 97%
“…This finding in the present study contradicts the findings of other studies [24][25][26][27], which emphasized that the HBM variables overly depended on psychological factors rather than focusing on cultural values, myths, misconceptions and prejudices, which typically predict human behavior [28].…”
Section: Discussioncontrasting
confidence: 97%
“…This study also reported that medical doctors had better knowledge than other professional groups, whereas cleaning staff had disquietingly inadequate knowledge. These findings are in line with previous studies [ 22 24 ]. This might be due to higher technical knowledge among medical doctors than other professional groups.…”
Section: Discussionsupporting
confidence: 94%
“…for reselling despite the deadly health risks. It has been reported that the re-use of syringes can even cause the spread of infections such as AIDS and hepatitis [1,17]. One estimate shows that some 5.2 million people (including 4 million children) die each year from waste related diseases in Bangladesh.…”
Section: Resultsmentioning
confidence: 99%